2020
DOI: 10.1002/esp.4751
|View full text |Cite
|
Sign up to set email alerts
|

Time‐transgressive cryoplanation terrace development through nivation‐driven scarp retreat

Abstract: Cryoplanation terraces are elevated bedrock features resembling giant staircases, with alternating steep scarps and shallow sloping treads. These landscape‐scale features have long been associated with periglacial environments, but the processes involved in their formation remain vaguely specified and contentious. The two leading hypotheses for the formation of cryoplanation terraces are centered on: (1) geologic structure; and (2) nivation‐driven scarp retreat. The nivation‐formation hypothesis invokes scarp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 61 publications
5
20
0
Order By: Relevance
“…Owing to the similarity between the rates reported here and those from process-oriented nivation studies elsewhere, as well as ages synchronous with local glacial advances, we conclude that the nivation process suite is likely to have produced the CTs studied in this work during Quaternary cold intervals, thereby exposing these elevated boulders. The results presented here are also consistent with previous work by Nyland and Nelson (2019) that proposed a refined model for CT formation in eastern Beringia based on nivation after examining spatial trends in a variety of relative weathering indices across all terrace treads present at these two study sites.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Owing to the similarity between the rates reported here and those from process-oriented nivation studies elsewhere, as well as ages synchronous with local glacial advances, we conclude that the nivation process suite is likely to have produced the CTs studied in this work during Quaternary cold intervals, thereby exposing these elevated boulders. The results presented here are also consistent with previous work by Nyland and Nelson (2019) that proposed a refined model for CT formation in eastern Beringia based on nivation after examining spatial trends in a variety of relative weathering indices across all terrace treads present at these two study sites.…”
Section: Discussionsupporting
confidence: 91%
“…Cosmogenic 10 Be and 36 Cl geochronology of cryoplanation including, Kňažková et al (2018) who reported scarp retreat under nivation processes on James Ross Island, Antarctica, of 0.77 ± 0.12 mm/yr (0.077 ± 0.012 cm/yr), and Matthews et al (2019) who reported maximum rates of ∼0.1 mm/yr from Svartkampan, Jotunheimen, Norway. Indirect evidence also supports the nivation hypothesis for CT formation across eastern Beringia (Reger, 1975;Reger and Péwé 1976;Nelson, 1989Nelson, , 1998Nelson and Nyland, 2017;Nyland and Nelson 2019). Owing to the similarity between the rates reported here and those from processoriented nivation studies elsewhere, as well as ages synchronous with local glacial advances, we conclude that the nivation process suite is likely to have produced the CTs studied in this work during Quaternary cold intervals, thereby exposing these elevated boulders.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These less inclined sections, in turn, lose clarity and eventually merge with the surrounding slope surface. Jointing characteristics and cliff/slope morphology match the intact strength of basalt in the Muchów Hills in that tall vertical cliffs have developed in massive and mechanically stronger rocks (mean R-values from 53.8 ± 2.06 to 58.8 ± 3.25 SD), whereas lower R-values (from 47.3 ± 2.46 to 55.6 ± 3.26 SD) were recorded within less conspicuous rock steps supported by thinner columns.Low-inclination surfaces downslope from the bedrock cliffs, comparable to cryoplanation terraces,1,[34][35][36] are rare. The best examples of such benches can be found on the south-facing slopes, in the west-central part(Figure 2E).…”
mentioning
confidence: 99%